La fuerza de la literatura -novela- como justicia poética y el derecho - Munguía Salcedo, Salvador (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
It is a work that emphasizes the importance of literature for the law, demonstrating that through the philosophical reflection among law and literature many clues can be found to respond to the more primitive issues, simultaneously to the deepest of the legal matter: what is law?, How important is the relationship between law and literature? That is, extract from the literature its critical function. This work studies the law from other perspectives conceiving it further than its procedures and rules; the literature, what is looking for is to interpret the law through a profound analysis and constructs a critical reflection about different fundamental aspects of law, based on the valuable contributions of some experts in this matter. The most profitable relationship of the literature in law is that it contributes to identify and develop the group of moral virtues such as empathy, courage, generosity, justice, plus epistemic or intellectual virtues: the open minded, wisdom, practice, intellectual autonomy, that are necessary in learning, not only in the student but the law practitioner to rationalize correctly in the context of decision making. That is why, the reading of literary works, far from being irrelevant for a good jurisprudence formation, is a fundamental tool in the training of jurists and judges who have the necessary skills to perform their function and therefore, essential for a good administration of justice.

A través de la reflexión filosófica entre el derecho y la literatura se pueden hallar muchas claves para responder a las cuestiones más primigenias, a la vez que a las más profundas de lo jurídico: ¿qué es el derecho?, ¿qué importancia tiene la relación del derecho y la literatura? Es decir, extraer de la literatura su función crítica. Estudiar el derecho desde otras perspectivas al concebir al derecho más allá de lo dogmático, más allá de sus procedimientos y reglas; la literatura, lo que busca es interpretar el derecho a través de un análisis profundo y construye una reflexión crítica sobre diversos aspectos fundamentales del derecho, a partir de las valiosas aportaciones de algunos expertos en la materia. La relación más fructífera de la literatura en el derecho es su contribución a identificar y desarrollar el conjunto de virtudes morales tales como la empatía, la valentía, la generosidad, la justicia -entre otras-, además de virtudes epistémicas o intelectuales: la apertura de mente, la sabiduría práctica, la autonomía intelectual, que son necesarias en el aprendizaje no sólo del estudiante sino del practicante de derecho para razonar correctamente en el contexto de la toma de decisiones. Por ello, la lectura de obras literarias, lejos de ser irrelevante para una buena formación jurídica, es una herramienta fundamental en la formación de juristas y de jueces que tengan las capacidades necesarias para realizar adecuadamente su función y, por lo tanto, esencial para una buena administración de justicia.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2017-0387; Humanidades; Derecho; Literatura; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/796